Agglomeration economies, taxable rents and government capture: evidence from a place-based policy. (9th June 2017) - Brülhart, Marius; Simpson, Helen
Abstract: We study how industry-level agglomeration economies affect government policy. Using administrative data on firm subsidies in economically lagging regions of Great Britain, we contrast two alternative hypotheses. Economic geography models imply that firms at an industry's core can sustain higher tax burdens or require lower subsidies than firms in more remote locations. Conversely, political economy models predict firms at the industry's core to be more successful at lobbying government, particularly at the subnational level, thus obtaining more favourable fiscal treatment. Our evidence suggests that local government agencies structure subsidy offers to favour pre-existing employment in locally agglomerated industries, behaviour more in line with theories of policy capture than with economic geography models. Grants administered by central government agencies, however, conform more strongly with the predictions of economic geography models.